Is aging a disease? The theoretical definition of aging in the light of the philosophy of medicine - Saborido, Cristian; García-Barranquero, Pablo (My University, 2019)
In this talk, I attempt to shed light on the philosophical debate about the theoretical definition of aging from the discussion of the notion of disease in the philosophy of medicine. As a result, I introduce a concrete approach -- the pragmatist approach to aging -- to account for the theoretical relationship between the notions of disease and aging, as they are addressed in the philosophy of aging. To that end, the structure of this work is as follows: first, in section 2, I analyze the discussion between the two major positions in this debate, and introduce the influential accounts of authors such as Hayflick, Schramme, Caplan, Murphy, and Callahan & Topinkova. I will show that in this discussion it is being assumed by some authors that the definition of disease is univocal and corresponds to what some of these authors understand as a "non-natural state". The motivation of this is straightforward: in order to decide if aging should be defined as a disease we need to clarify first what a disease is and what implies to characterize something as such. In section 3, I will show that the disagreement between those who argue that aging is a disease and those who claim that it is not is ultimately based on an assumption of different notions of disease. In addition, I will also turn to the debate on disease in the philosophy of medicine to analyze the proposals of Callahan & Topinkova and Murphy. These authors advocate avoiding the question of whether or not aging is a disease for pragmatic reasons. The important thing would not be to define aging as a disease but to medically treat it as such. I propose to reformulate this proposal of pragmatic motivation to frame it in an approach to the concept of disease, which I call "pragmatist", that has advocated philosophers of medicine such as Cooper or Hofmann. I think that this pragmatist approach addresses the issue of medical categorization of aging in a more scientific and philosophical fruitful way.
Keywords: Envejecimiento - Filosofía; Medicina - Filosofía; Enfermedades - Factores de edad - Filosofía; Aging; Disease